2023
DOI: 10.1186/s12967-022-03842-5
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) ameliorates sepsis-induced cardiomyopathy by alleviating inflammatory response and mitochondrial damage through the NF-κB and MAPK pathways

Abstract: Background There is no available viable treatment for Sepsis-Induced Cardiomyopathy (SIC), a common sepsis complication with a higher fatality risk. The septic patients showed an abnormal activation of the renin angiotensin (Ang) aldosterone system (RAAS). However, it is not known how the Ang II and Ang-(1–7) affect SIC. Methods Peripheral plasma was collected from the Healthy Control (HC) and septic patients and Ang II and Ang-(1–7) protein concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 80 publications
2
7
0
Order By: Relevance
“…Empagliflozin did not exhibit the ability to inactivate NF-κB signaling molecules, but it had the ability to inhibit p38 MAPK and ERK1/2 activity [ 19 ]. The MAPK signaling pathway is involved in oxidative stress [ 63 ], inflammatory responses [ 64 ], and cell proliferation [ 65 ], a finding that confirms the study of Lin et al [ 66 ]. The results of this study suggest that the inhibitory effect of columbamine (Col) on HCC is associated with the p38 MAPK and ERK1/2 signaling pathways [ 66 ].…”
Section: Empagliflozin and Cancersupporting
confidence: 56%
“…Empagliflozin did not exhibit the ability to inactivate NF-κB signaling molecules, but it had the ability to inhibit p38 MAPK and ERK1/2 activity [ 19 ]. The MAPK signaling pathway is involved in oxidative stress [ 63 ], inflammatory responses [ 64 ], and cell proliferation [ 65 ], a finding that confirms the study of Lin et al [ 66 ]. The results of this study suggest that the inhibitory effect of columbamine (Col) on HCC is associated with the p38 MAPK and ERK1/2 signaling pathways [ 66 ].…”
Section: Empagliflozin and Cancersupporting
confidence: 56%
“…Moreover, DENND2D serves as a tumor suppressor across several cancer types and disrupts MAPK signaling within tumor cells 20 , 21 . Notably, the MAPK pathway mitigates inflammation and mitochondrial damage associated with sepsis, suggesting a potential beneficial impact of DENND2D on sepsis outcomes 22 . Comprehensive research is required to delineate DENND2D’s function in sepsis more clearly and to assess its viability as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is known to exhibit pro-apoptotic effects in certain stimulated cell environments [ 67 ]. Inhibition of cardiomyocyte apoptosis mediated by NF-κB signaling pathway has a potential protective effect on sepsis induced cardiomyopathy [ 68 ]. Additionally, it has been suggested that the surge of inflammatory response during sepsis is dependent on the activation of NF-κB signaling pathway [ 50 ].…”
Section: Discussionmentioning
confidence: 99%